Language Teaching Research & Language Pedagogy. - Ellis, Rod (John Wiley & Sons Inc, 2012)
This book examines current research centered on the second language classroom and the implications of this research for both the teaching and learning of foreign languages. It offers illuminating insights into the important relationship between research and teaching, and the inherent complexities of the teaching and learning of foreign languages in classroom settings.